A National Health Service (letter) - Roberts, Bryn, 1897-1964
1944-06-06 1944 1940s 2 pages TELEPHONE: LEE GREEN 2842-5 (4 Lines) National Union of Public Employees Late National Union of Corporation Workers Registered No. 1386 T. Incorporating the National Association of Nurses 8, Aberdeen Terrace, Blackheath, London, S.E.3. GENERAL SECRETARY: BRYN ROBERTS TO WHOM ALL COMMUNICATIONS SHOULD BE ADDRESSED YOUR REF. WMC/NA/EMG/495 OUR REF. R/EH Women's Department. The Rt. Hon. Sir Walter Citrine, K.B.E., 6th June, 1944. General Secretary, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Sir Walter, A NATIONAL HEALTH SERVICE Thanks for your letter of the 2nd June, in which you invite the Union to submit its comments upon the Government's White Paper outlining proposals for a National Health Service, preparatory to such proposals being considered by your Council. In responding I wish to state that, in the main, the [Union] National Union of Public Employees commends the proposals which, if implemented, will certainly lead to a more efficient hospital and medical service than that now obtaining. It notes, however, that while the White Paper rightly devotes considerable attention to the welfare of the doctors and reiterates the undertaking not to injure their interests, the nursing and subordinate staffs, who are no less essential to the administration of such a Health Service as envisaged, are dismissed in a cursory reference of a single sentence. The Rushcliffe rates which are recommended certainly fall far short of what nurses should receive, while the Hetherington rates are but a miserable pittance. As an effective National Health Service will largely depend upon an efficient and contented staff, and as this is impossible to achieve on the wage rates suggested, it is essential that special attention should be given to effecting adequate wage standards for those engaged in such services. The Union also believes that having regard to the character of the duties of the nursing and other grades, which duties are often dreary and monotonous, a 40 hour working week should be instituted at the end of hostilities, when the proposals of the White Paper become operative. It is believed, too, that the wages and conditions of those within the present hospital and institutional services, and in any reformed Health Service which is contemplated, will never be satisfactorily dealt with in the absence of a properly constituted National Board that will determine such wages on a national and not an area or single hospital basis, as is the case at present. 292/847/2/59